Evolution of antifungal drug tolerance in Candida albicans - Brinco, Catarina Alexandra Gomes (2020)
Nowadays, fungal infections are a serious public health issue due to the increasing drug resistance and small number of antifungals available. Candida albicans is the most prevalent human fungal pathogen, causing invasive fungal infections that are associated with high mortality rates. This fungus has a particular hybrid tRNA (tRNACAGSer) that is recognized by both the leucyl - and the seryl-tRNA synthetases (LeuRS and SerRS), allowing for incorporation of leucine (3%) and serine (97%) at CUG positions. It has already been shown that in the presence of antifungals, the level of Leu misincorporation increases up to 20% and that hypermistranslating strains have higher tolerance to drugs, namely azoles, which includes fluconazole. In this study, we tested the hypothesis that mistranslation could be directly linked with the appearance of drug tolerant subpopulations of C. albicans cells from which, with prolonged drug treatment, resistance may emerge. In order to understand if antifungals can select subpopulations of tolerant cells, we carried out in vitro competition experiments with fluorescently tagged C. albicans strains that were experimentally evolved with or without fluconazole during 400 generations. A wild-type strain (T0) was tagged with mCherry while hypermistranslating strains were tagged with GFP which allowed strain differentiation within the competition. Results showed an increase of hypermistranslating cells during evolution in the presence of the antifungal, but no significative alteration of the minimal inhibitory concentration (MIC) value was detected. On the other hand, microcolonies (constituted exclusively by hypermistranslator cells) appeared within the inhibition ellipse of the E test, suggesting the emergence of tolerance instead of resistance. These results suggest that prolonged antifungal therapy may select hypermistranslating clones that drive the appearance and persistence of tolerant cells within the population. Tolerance phenotypes may not be detected through significative MIC alterations but it must be taken into consideration since it could be associated with recurrent candidiasis